2009
DOI: 10.1016/j.jenvp.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal pessimism and spatial optimism in environmental assessments: An 18-nation study

Abstract: The personal assessments of the current and expected future state of the environment by 3232 community respondents in 18 nations were investigated at the local, national, and global spatial levels. These assessments were compared to a ranking of each country’s environmental quality by an expert panel. Temporal pessimism (“things will get worse”) was found in the assessments at all three spatial levels. Spatial optimism bias (“things are better here than there”) was found in the assessments of current environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
190
5
42

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(259 citation statements)
references
References 22 publications
15
190
5
42
Order By: Relevance
“…Participants in research by Boniecki (1980), Hoogstra andSchanz (2009), andSimons et al (2004) showed a lack of engagement with events on a temporal extent beyond 10-15 years. In contrast to this spatial and temporal "myopia," a "hyperopia" has been found linked to both scales in terms of problem recognition (Gifford et al, 2009;Uzzell, 2000): the longer term future was seen as more problematic than the shorter term by participants in these studies, and global concerns were seen as more problematic than local issues. Other psychological research has dealt with personal views of temporal and geographic scale related to environmental change concerns (Gifford et al, 2009;Lima & Castro, 2005;Uzzell, 2000), but this research has not been operationalized to provide direct input for a participatory social-ecological systems governance context.…”
Section: Perspectives On Scale Dynamics In Socialecological Systems Gcontrasting
confidence: 61%
“…Participants in research by Boniecki (1980), Hoogstra andSchanz (2009), andSimons et al (2004) showed a lack of engagement with events on a temporal extent beyond 10-15 years. In contrast to this spatial and temporal "myopia," a "hyperopia" has been found linked to both scales in terms of problem recognition (Gifford et al, 2009;Uzzell, 2000): the longer term future was seen as more problematic than the shorter term by participants in these studies, and global concerns were seen as more problematic than local issues. Other psychological research has dealt with personal views of temporal and geographic scale related to environmental change concerns (Gifford et al, 2009;Lima & Castro, 2005;Uzzell, 2000), but this research has not been operationalized to provide direct input for a participatory social-ecological systems governance context.…”
Section: Perspectives On Scale Dynamics In Socialecological Systems Gcontrasting
confidence: 61%
“…Research shows that environmental problems are often perceived as remote rather than as immediate threats (e.g. Gifford et al, 2009;Spence, Poortinga, & Pidgeon, 2012), which could be the reason behind why the strength of stated behavioural intentions was more sensitive to individual differences in CFC-Future than in CFC-Immediate.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies show the relevance of place-based, or locally anchored, psychological processes, such as place attachment and place identity, for various global change-related pro-environmental attitudes and behaviors. Examples include the reduction of water consumption (Bonaiuto et al, 2008), the support of biodiversity conservation policies Carrus et al 2005 (Gifford et al 2009). Local norms affecting specific pro-environmental choices, such as home waste recycling (Fornara et al, 2011) or towel reuse by hotel guests (Goldstein et al, 2008) are also specific to clearly defined locations.…”
Section: Linking Place-based Research To Global Environmental Trendsmentioning
confidence: 99%